2002
DOI: 10.1128/iai.70.12.6707-6714.2002
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Responses to theMycobacterium tuberculosis-Specific Antigen ESAT-6 in Brazilian Tuberculosis Patients

Abstract: The Mycobacterium tuberculosis-specific ESAT-6 antigen induces highly potent T-cell responses and production of gamma interferon (IFN-␥), which play a critical role in protective cell-mediated immunity against tuberculosis (TB). In the present study, IFN-␥ secretion by peripheral blood mononuclear cells (PBMCs) in response to M. tuberculosis ESAT-6 in Brazilian TB patients was investigated in relation to clinical disease types, such as pleurisy and cavitary pulmonary TB. Leprosy patients, patients with pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 44 publications
(42 reference statements)
7
55
1
3
Order By: Relevance
“…It has been reported that BCG vaccination of human newborns induces a specific IFN-cþ CD8þ T cell response to BCG in vitro, although it is quantitatively smaller than the CD4þ T cell response (27). Regarding the non-Target cells (IFN-cþ CD4À T cells) positive case in the no TB group of this study, the significance of increased MTB antigen-stimulated IFN-c-producing CD8þ T cells should be elucidated in further studies (6,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that BCG vaccination of human newborns induces a specific IFN-cþ CD8þ T cell response to BCG in vitro, although it is quantitatively smaller than the CD4þ T cell response (27). Regarding the non-Target cells (IFN-cþ CD4À T cells) positive case in the no TB group of this study, the significance of increased MTB antigen-stimulated IFN-c-producing CD8þ T cells should be elucidated in further studies (6,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The ICCFC has the advantage of identifying the composition of the secreting cells to reference populations of peripheral blood (2,6,(9)(10)(11)(12)(13)(14), bronchoalveolar lavage fluid (9,15), or induced sputum (16) using polychromatic immunophenotyping. Despite the obvious advantage of diagnostic accuracy, studies comparing ICCFC with two other methodologies have not yet been performed (7), with the exception of two recent reports, one with QFT (14), and the other with ELISpot (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the low-molecular-mass potent T-cell antigens identified by Andersen and colleagues, early secretory antigen target 6 (ESAT-6) and culture filtrate protein 10 (CFP10), are encoded in RD1 (2, 10) and have been intensively investigated in animal models and humans over the last few years (4,7,15,16,26,30,32,33,36,40). Studies using several different assays, including lymphoproliferation, gamma interferon (IFN-␥) enzyme-linked immunosorbent assay (ELISA), and IFN-␥ enzyme-linked immunospot (ELISPOT) assay, have shown that they are strong targets of the cellular immune response in animal models, TB patients, and contacts (4,11,24,28,30,35,(37)(38)(39).…”
mentioning
confidence: 99%
“…Pulmonary tuberculosis and leprosy were diagnosed according to the criteria established by the World Health Organization (WHO) and the Brazilian Ministry of Health. The detailed methodology for the screening and diagnosis of the tuberculosis and leprosy patients has been described elsewhere (15,16). The patients were treated according to the recommendations of the Ministry of Health.…”
Section: Study Populationmentioning
confidence: 99%